MADU DALAM PERSPEKTIF AL-QUR'AN DAN SAINS MODERN: ANALISIS QS. AN-NAHL AYAT 68-69 DAN TEMUAN PETER MOLAN TENTANG MANFAAT TERAPIUTIK MADU - Isqi, Nabil; Nasikhin, Naskhin; Bisri, Kasan (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2025)
Honey has long been recognized as a natural substance with therapeutic benefits, both in the Qur'anic perspective and modern medicine. This study aims to analyze the alignment between the Qur'anic view (QS. An-Nahl verses 68-69) of honey as a "healing for mankind" and modern scientific findings, particularly Peter Molan's research on its antibacterial mechanisms and wound-healing properties. A qualitative literature review method was employed, integrating Qur'anic exegesis analysis and a review of scientific literature from reputable databases such as PubMed and ScienceDirect. The results demonstrate that honey's therapeutic properties, including antibacterial activity, wound healing, and potential as an antibiotic alternative, have been scientifically validated through active compounds like methylglyoxal (MGO) and hydrogen peroxide (H₂O₂). These findings align with the Qur'anic description and its interpretations, while also highlighting challenges in quality standardization for clinical applications. In conclusion, this study strengthens the integration of science and religion in understanding honey as a therapeutic agent and recommends the development of standardized protocols and further research to optimize its use in modern healthcare.